Notice: Payments for answers will end 4/10/2017. Click for more info.
You have new items in your feed. Click to view.
Question and answer
Q: Multiply:(5x + 1)(2x - 2)
A: (5x + 1)(2x - 2) = 10x^2 - 10x + 2x - 2; = 10x^2 - 8x - 2
Get an answer
Original conversation
User: Multiply:(5x + 1)(2x - 2)





Weegy: 10x -10x +2x -2 = 2x -2
Expert answered|MoStWaNteD|Points 1677|

Question
Asked 10/1/2010 5:21:44 PM
Updated 12/1/2014 6:13:31 AM
1 Answer/Comment
This conversation has been flagged as incorrect.
Flagged by alfred123 [12/1/2014 6:13:30 AM]
New answers
Rating
3
(5x + 1)(2x - 2)

= 10x^2 - 10x + 2x - 2;

= 10x^2 - 8x - 2
Added 12/1/2014 6:13:31 AM
This answer has been confirmed as correct and helpful.
Confirmed by andrewpallarca [12/1/2014 6:23:50 AM]
Comments

There are no comments.

Add an answer or comment
Log in or sign up first.
Questions asked by the same visitor
Solve:11b - 6 = 10b + 4
Weegy: 11b - 6 = 10b + 4; 11b - 10b = 4 + 6; b = 10 (More)
Question
Expert Answered
Updated 4/13/2014 8:35:19 AM
1 Answer/Comment
Solve: z - 6.68 = 7.47
Question
Not Answered
Updated 4/13/2014 8:34:42 AM
2 Answers/Comments
z=14.15
Added 9/26/2010 1:20:13 PM
z - 6.68 = 7.47;

z = 7.47 + 6.68;

z = 14.15
Added 4/13/2014 8:34:42 AM
This answer has been confirmed as correct and helpful.
Simplify: 10x - 2 + 3x
Weegy: 10x - 2 + 3x = 13x - 2 (More)
Question
Expert Answered
Updated 12/1/2014 6:24:23 AM
0 Answers/Comments
Simplify: 10x - 2 + 3x
Weegy: 10x - 2 + 3x = 13x - 2 User: Simplyfy the following expression: 9(a + 8) - 5 (a - 10) (More)
Question
Not Answered
Updated 4/30/2014 4:07:54 PM
2 Answers/Comments
10x - 2 + 3x = 13x -2

9(a+8) - 5(a-10) = 9a + 72 - 5a + 50 = 4a + 122

Note: Multiplication of the same sign is positive (+).
Added 9/26/2010 3:00:30 PM
9(a + 8) - 5 (a - 10);

9a + 72 - 5a + 50

= 4a + 122
Added 4/30/2014 4:07:54 PM
This answer has been confirmed as correct and helpful.
Add the following: (5x2 + x + 7) + (3x2 - 4x + 3)
Weegy: Did you copy this problem correctly. Are you by chance missing an = sign? (More)
Question
Expert Answered
Updated 6/26/2014 6:22:30 PM
1 Answer/Comment
(5x^2 + x + 7) + (3x^2 - 4x + 3)

= 5x^2 + 3x^2 + x - 4x + 7 + 3;

= 8x^2 - 3x + 10
Added 6/26/2014 6:22:30 PM
This answer has been confirmed as correct and helpful.
Confirmed by jeifunk [6/26/2014 10:00:16 PM]
27,011,251 questions answered
*
Get answers from Weegy and a team of really smart lives experts.
S
L
Points 254 [Total 272] Ratings 0 Comments 184 Invitations 7 Offline
S
L
R
Points 135 [Total 286] Ratings 1 Comments 5 Invitations 12 Offline
S
L
Points 130 [Total 130] Ratings 0 Comments 130 Invitations 0 Offline
S
R
L
R
P
R
P
R
Points 66 [Total 734] Ratings 0 Comments 6 Invitations 6 Offline
S
1
L
L
P
R
P
L
P
P
R
P
R
P
R
P
P
Points 62 [Total 13329] Ratings 0 Comments 62 Invitations 0 Offline
S
L
1
R
Points 34 [Total 1450] Ratings 2 Comments 14 Invitations 0 Offline
S
L
Points 10 [Total 187] Ratings 0 Comments 0 Invitations 1 Offline
S
Points 10 [Total 13] Ratings 0 Comments 10 Invitations 0 Offline
S
Points 10 [Total 10] Ratings 0 Comments 0 Invitations 1 Offline
S
Points 2 [Total 2] Ratings 0 Comments 2 Invitations 0 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.